Grammatical Cohesive Devices in “The Secret” by Rhonda Byrne - Muhajir Hilmi Fathani; Deden Novan Setiawan Nugraha (Budapest International Research and Critics University, 2022)
The research aimed to analyze the types and meaning of grammatical cohesive devices used in the book “The Secret” by Rhonda Byrne. This research used the qualitative descriptive method with theory from Sukardi (2003). In analyzing the data, this analysis used the theory of discourse analysis from Halliday and Hasan (1976), and Gerot and Wignell (1994). The result of this research shows that there are 50 data of grammatical cohesive devices found in the book “The Secret” including reference with 18 data (36%), substitution with 4 data (8%), conjunction with 27 data (56%), and ellipsis with 1 data (2%). Based on the analysis, each grammatical cohesive device used in the book “The Secret” by Rhonda Byrne has a different meaning or explanation according to the type of grammatical cohesive device used. Conjunction is used to link the sentences together. Reference is used to avoid repetition in relation to meanings. Substitution is used to ignore the repetition of words. Ellipsis is used to omit unnecessary words.